2018
DOI: 10.1002/adma.201800534
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Materials, Devices, and Systems for Neural Interfaces

Abstract: Technologies capable of establishing intimate, long-lived optical/electrical interfaces to neural systems will play critical roles in neuroscience research and in the development of nonpharmacological treatments for neurological disorders. The development of high-density interfaces to 3D populations of neurons across entire tissue systems in living animals, including human subjects, represents a grand challenge for the field, where advanced biocompatible materials and engineered structures for electrodes and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
137
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 186 publications
3
137
0
2
Order By: Relevance
“…Natural micromovements of brain tissues may induce intense stress and inflammation at the interface, where the glial sheath forms to gradually screen signals out . Extensive studies in the last decade have demonstrated that flexible polymer‐based neural probes, which are compliant with brain tissues, can reduce the mechanical interfacial mismatch and are the ideal tool for chronic implantation . However, the low stiffness of flexible neural probe makes it susceptible to bending and buckling during insertion into the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural micromovements of brain tissues may induce intense stress and inflammation at the interface, where the glial sheath forms to gradually screen signals out . Extensive studies in the last decade have demonstrated that flexible polymer‐based neural probes, which are compliant with brain tissues, can reduce the mechanical interfacial mismatch and are the ideal tool for chronic implantation . However, the low stiffness of flexible neural probe makes it susceptible to bending and buckling during insertion into the brain.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Extensive studies in the last decade have demonstrated that flexible polymer-based neural probes, which are compliant with brain tissues, can reduce the mechanical interfacial mismatch and are the ideal tool for chronic implantation. [8][9][10] However, the low stiffness of flexible neural probe makes it susceptible to bending and buckling during insertion into the brain. To deal with this dilemma, several delicate strategies have been developed to guide the insertion such as transient shuttles [11][12][13][14][15][16] with dissolvable support materials such as silk, sugars, hydrogel or polyethylene glycol (PEG) as coatings, metal as rigid backbone layers for insertion, [17][18][19] and removable shuttles [20][21][22][23] with SU-8 shanks or microneedles as temporary carriers.…”
Section: Introductionmentioning
confidence: 99%
“…However, advanced convergence systems that directly employ display‐based sensing or treatment solutions are now receiving growing interests. This new generation of technologies seems to result from the discovery of multifunctionality in materials and devices as well as the promotion of interdisciplinary investigations that create unconventional applications . In this review, we provide an overview of recent literature that demonstrates the emergence of display‐based biotechnology and novel healthcare platforms.…”
Section: Introductionmentioning
confidence: 99%
“…This new generation of technologies seems to result from the discovery of multifunctionality in materials and devices as well as the promotion of interdisciplinary investigations that create unconventional applications. [3][4][5][6][7] In this review, we provide an overview of recent literature that demonstrates the emergence of display-based biotechnology and novel healthcare platforms. Although still being at its early stage, the projected broad applicability and unique features are expected to stimulate a rapid growth of this technology, and this article will categorize and highlight some of the most noticeable systems reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The recent advances in 3D mesostructures have given rise to a number of intriguing devices that exhibit unique features, which have broad applications in flexible electronics, photonics, mechanics, and biomedicine . Among various fabrication techniques, rolled‐up nanotechnology is an innovative method that constructs 3D tubular micro/nanostructures out of planar nanomembranes from the top‐down perspective.…”
mentioning
confidence: 99%